Understanding Parental Behaviours Related to Infant Sleep Environment: A Qualitative Study - Jennifer N. Smith; Julie C. Johnstone; Sanjay Mahant; Michelle Shouldice (Child: Care, Health and Development, 2026)
ABSTRACT Introduction Sudden unexplained death in infants is responsible for a significant proportion of infant deaths. Despite broad dissemination of Canadian Paediatric Society and American Academy of Paediatrics safe sleep recommendations, studies demonstrate significant caregiver nonadherence. Few studies have examined caregiver reasons for low uptake of recommendations. Objectives Our study aimed to explore parental perceptions, beliefs and influences regarding safe infant sleep environment and factors contributing to parental behaviour related to sleep environment. Methods A qualitative study utilizing grounded theory methodology was conducted with in‐depth individual interviews of parents of infants less than 6 months admitted to a large paediatric hospital in Toronto, Canada. Data collection occurred from November 2017 to January 2018 until saturation of themes. Interview transcripts were analysed for recurrent and emergent themes and a coding structure was developed. Results Interviews with 14 caregivers were completed. Caregivers described a range of sleep locations and environments. Decisional conflict was a dominant theme that emerged, as caregivers reported multiple factors simultaneously affecting decision‐making about sleep location and often acting in opposition with one another. Factors influencing decision‐making were categorized into the following themes: (1) safety, (2) feasibility and family logistics and (3) perception of infant preference and developmental needs. Information sources regarding sleep choices typically included family, friends, healthcare providers and media. Conclusion These results can inform healthcare providers counselling about safe sleep recommendations and public health interventions aimed at increasing adherence to safe sleep recommendations and reducing preventable infant deaths.